PENERAPAN METODE RUP UNTUK MENGANALISIS SISTEM E-KONSELING (STUDI KASUS SMP NEGERI 6 KOTA SORONG) - Dinda Irdayani Soulisa (LPPM Politeknik Saint Paul Sorong, 2023)
Problem Formulation How to analyze the E-Counseling System for problematic student data? And how to input problematic student service data in the E-Counseling System. The purpose of this study is to analyze the E-Counseling System for data on students with problems at SMP Negeri 6 Kota Sorong. This type of research is included in the type of qualitative method research, namely as a method that is analyzed systematically by describing the results of the research. RUP is an iterative approach to software that focuses on architecture (architecture-centric), by implementing object-oriented data and activities focusing on model expansion. RUP is more directed at use cases (use case driven). RUP method. Counseling Guidance is an assistance service for students, both individually and in groups, so that they are independent and develop optimally. SMP Negeri 6 Kota Sorong is one of the schools that implements guidance and counseling services. Basically this counseling guidance is intended for students who often commit violations at school, so that they can help the school, especially the counseling guidance section in searching for guidance student data and making fast and accurate reports. The system development method uses the RUP method. This system uses the PHP and MySQL programming languages ​​as database servers which are summarized in one Xampp application. Problems that occur in processing student data with problems in guidance and counseling at SMP Negeri 6 Kota Sorong currently still use manual data which is still written in the violation book of problematic students